Upregulation of SGLT1 and 2 promotes oxidative stress in right atrial appendages of patients with low-grade inflammatory responses: potential role in atrial fibrillation. (3rd October 2022) - Fakih, W; Mroueh, A; Auger, C; Kindo, M P; Mommerot, A; Mazzucotelli, J P; Pieper, M P; Ohlmann, P; Morel, O; Schini-Kerth, V; Jesel, L
Abstract: Introduction: Atrial fibrillation (AF), the most common cardiac arrhythmia, is associated with increased morbidity and mortality. Inflammatory infiltrates have been observed in atrial tissues from AF patients suggesting that low-grade inflammation contributes to the pro-fibrotic, pro-remodeling and pro-senescence responses of the atrial tissue favoring AF. Although sodium glucose co-transporter2 inhibitors (SGLT2i) have shown beneficial effects in heart failure, the expression and role of SGLT2 in cardiac tissues remain unclear. Purpose: This study examined the expression of SGLT1 and 2 in right atrial appendages (RAA) of cardiac patients, and, if so, to determine the underling mechanism and their functional role. Methods: RAA were harvested from patients undergoing coronary artery bypass surgery or aortic valve replacement at the University Hospital of Strasbourg. Patients with comorbidities such as malignancies and chronic inflammatory diseases were excluded. The expression level of markers was assessed using RT-qPCR, Western blot analysis, and immunofluorescence staining, and the level of reactive oxygen species using dihydroethidium staining. Results: Analysis of RAA samples evidenced up-to a 4-fold difference in the NOS3 mRNA level. Those with low levels of NOS3 mRNA showed high levels of ICAM1, F3, MMP9, TGF-β1, TP53, CDKN1A, CDKN2A, SLCA1, SLCA2, IL1B, IL6, TNF-a and CD68 whereas the contrary was observed in those with high levels of NOS3 mRNA. SGLT1/2 mRNA levels were negatively correlated with that of eNOS and positively with those of IL-1, IL-6, TNF- α, CD68, and the senescence marker p53. Western blot analysis of RAA indicated that those expressing low levels of eNOS protein showed high levels of ICAM-1, VCAM-1, TF, MMP-2, TGF-b, SGLT1, SGLT2, p-p65, p53, p21 and p16 proteins whereas the contrary was observed in those with high levels of eNOS protein. Immunofluorescence staining indicated that SGLT1/SGLT2 signals were colocalized with those of CD31, an endothelial cell marker, in RAA, and associated with those of CD68 and TNF-α. Samples with high levels of SGLT1 and 2 displayed higher levels of oxidative stress that were inhibited by the antioxidant NAC (N-acetylcysteine), VAS-2870 (NADPH oxidase inhibitor), perindoprilat (ACE inhibitor), losartan (AT1R antagonist), empagliflozin (selective SGLT2 inhibitor), sotagliflozin (dual SGLT1/2 inhibitor) and by infliximab (TNF-α receptor neutralizing antibody). Conclusion: The findings indicate that high expression levels of SGLT1 and 2 are observed in RAA showing low eNOS levels associated with pro-inflammatory, pro-senescent, pro-remodeling and pro-fibrotic responses. They were further associated with increased levels of oxidative stress sensitive to inhibitors of either the local angiotensin system, TNF-alpha or SGLT2. Thus, inhibition of SGLT2 appears to be an interesting approach to reduce the stimulatory pro-oxidant signal in atrium related to low-grade inflammation. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Boehringer Ingelheim Pharma GmbH & Co. KG